Answer:
k = 4
Step-by-step explanation:
Given equation:
[tex]\dfrac{(\sqrt{3})^{5}}{(\sqrt{3})^{-4}}=(\sqrt{3})^{(2k+1)}[/tex]
[tex]\textsf{Apply exponent rule} \quad \dfrac{a^b}{a^c}=a^{b-c}:[/tex]
[tex]\implies (\sqrt{3})^{(5-(-4))}=(\sqrt{3})^{(2k+1)}[/tex]
[tex]\implies (\sqrt{3})^{9}=(\sqrt{3})^{(2k+1)}[/tex]
[tex]\textsf{Apply exponent rule} \quad a^{f(x)}=a^{g(x)} \implies f(x)=g(x):[/tex]
[tex]\implies (\sqrt{3})^{9}=(\sqrt{3})^{(2k+1)}[/tex]
[tex]\implies 9=2k+1[/tex]
[tex]\implies 2k=8[/tex]
[tex]\implies k=4[/tex]